The Diversification of Scales of Horizontal Gender Segregation in the OECD Countries - Domagała, Wiktoria (Studia Oeconomica Posnaniensia, 2017)
The aim of the paper is to evaluate the scale of horizontal gender segregation in highly developed countries, belonging to the Organisation of Economic Cooperation and Development. Moreover, the paper assumes that the scale of this phenomenon differentiates the analysed countries and the observed changes are barely dynamic. The time scope of the empirical study covers the period between 1990 and 2014. In the first part, the paper presents a cluster analysis, which is significant to make an exact classification of the OECD countries in respect of occupational gender inequality. Secondly, the paper shows the employment pattern according to gender and economic sectors as well as the amount of feminisation. Next, the paper takes into consideration and evaluates the diversification of scales of horizontal gender segregation in the clusters of the OECD countries. To sum up, the most important conclusions and recommendations are shown.